How does export compliance influence the internationalization of firms: Is it a thread or an opportunity? - Vahid Jafari Sadeghi; Paolo Pietro Biancone; Charles Giacoma; Silvana Secinaro (Journal of Global Entrepreneurship Research, 2018)
Internationalization is a complex process, in which firms face various challenges that may lead to opportunities or threads. One of these challenges is export compliance. The objective of this paper is to disentangle the nature of export compliance and its function in international entrepreneurship. This study outlines a perspective on the export control system, discusses the most relative legislation, reveals the consequences of non-compliance and provides a case study and finally explains the function of export compliance in the international activities of firms.
Keywords: 650; internationalization; export compliance; international entrepreneurship; dual-use; money laundering; Iran